The Influence Of Price, Productivity, Islamic Financial Behavior, On The Welfare Of Palm Oil Farmers In Labuhan Batu - Iskandar, Irfan; Nasution, Juliana; Harahap, Muhammad Ikhsan (UNIVERSITAS PAKUAN, 2021)
This study aims to examine how the welfare of oil palm farmers in Labuhan Batu Regency is affected by prices, productivity, and Islamic financial behavior. The research employs multiple linear analysis and a quantitative descriptive approach. A total of 1,167 farmers participated, with a sample size of 80, determined using probability sampling. Primary data were gathered through a Likert-scale survey, while secondary data were sourced from books, journals, and prior studies. The results indicate that the F-test significance value is 0.000 0.05, and the independent factors explain 65.7% of the variance in farmers' welfare. The findings suggest that favorable prices and strong productivity improve income and ensure ample harvests. Islamic financial behavior supports sound financial management, allowing farmers to meet social obligations such as zakat while enhancing financial planning skills. In conclusion, the combination of price, productivity, and Islamic financial behavior fosters a positive environment for improving the welfare of oil palm farmers in Labuhan Batu.